1998
DOI: 10.1002/hep.510270319
|View full text |Cite
|
Sign up to set email alerts
|

Increased liver uptake of liposomes and improved targeting efficacy by labeling with asialofetuin in rodents

Abstract: To improve liposome-directed therapy of liver disease and gene delivery, it would be beneficial to selectively target hepatocytes. For this purpose, conventional liposomes (CL) were labeled with asialofetuin (AF), an asialoglycoprotein. The biodistribution of AF-labeled liposomes (AF-L) in mice and their incorporation into rat hepatocytes, and their potential use in acute liver injury, were investigated. AF-L displayed a quicker plasma clearance than CL, and 25.4%, 2.7%, and 1.2% of the injected dose remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 30 publications
(50 reference statements)
0
54
1
Order By: Relevance
“…28 [ 3 H]-Cholesterol was added into the lipid mixture before hydration according to a method described previously. 28 The size distribution of three formulations of cationic liposomes before mixing with plasmid DNA was between 200 and 300 nm.…”
Section: Chemicalsmentioning
confidence: 99%
“…28 [ 3 H]-Cholesterol was added into the lipid mixture before hydration according to a method described previously. 28 The size distribution of three formulations of cationic liposomes before mixing with plasmid DNA was between 200 and 300 nm.…”
Section: Chemicalsmentioning
confidence: 99%
“…1 Asialofetuin (AF), a glycoprotein having triantennary galactose terminal sugar chains, is known as an excellent ligand molecule selectively recognized by ASGPr. 2 For liver gene delivery, both virus-mediated [3][4][5] and non-viral systems have been considered. Although some of the virus-mediated gene transfer systems have been found to be quite effective, their usefulness is limited, given that they induce an immune response, leading to the rapid rejection of transduced cells.…”
Section: Introductionmentioning
confidence: 99%
“…After intravenous administration, asialofetuin-modified liposomes were rapidly eliminated from the blood, and most were recovered from the liver [129]. Intrahepatic distribution studies revealed that asialofetuin-modified liposomes were selectively found in liver parenchymal cells [130] and Wu et al reported that asialofetuin-modified liposomes distributed in the liver in combination with intravenously injected vitamin E improved the protective effect against CCl4-induced acute liver injury in mice [130].…”
Section: Galactosylated Liposomesmentioning
confidence: 99%